KOMUNIKASI TERAPEURIK DALAM KESEHATAN GIGI DAN MULUT DI RSGM LADOKDI TNI AL R.E. MARTADINATA - handayani, Farida (THERA-DENT (jurnal terapis gigi dan mulut), 2023)
Communication in nursing can be known as therapeutic communication which aims to help clients solve problems, or encourage clients to take good actions for healing and improving their health. In fact, there are still dental and oral therapists who do not carry out therapeutic communication. Objective: to find out the description of the application of therapeutic communication in dental and oral examinations. Methods: Descriptive analytic method with "cross sectional" approach. The sampling technique is "total sampling". Results: The results showed that in the application of therapeutic communication to dental and oral therapists with a good category 28 (84.8%) and a bad category 5 (15.2%). In the pre-interaction phase, 33 respondents (100%) were in the good category, in the orientation phase, the good category was 32 respondents (97%), in the work phase, the category was not good, 1.2 respondents (3.63%), in the categorical termination phase either 32.4 respondents (99%). Characteristics of respondents based on gender with good categorization for therapeutic communication carried out by women with 21 respondents (63.6%), characteristics based on age with good categorical namely age 36-45 years 15 respondents (45.5%), characteristics based on education level with good categorization, namely D3 32 (97.0%), characteristics based on length of service with good categorization, namely > 3 years 32 (97.0%). Conclusion : the conclusion of this study is that the application of therapeutic communication has been carried out well in the pre-interaction phase.